Publication of Linked Open Data – A Systematic Literature Review for Identifying Problems and Technical Tools Supporting the Process - Silva Aguilar, Jairo H. (2023)
On the Internet, we find a large amount of information from government institutions that has been published in open format. However, only a part of these data is available in standard formats such as Resource Description Framework (RDF), and to a lesser extent, is published as Linked Open Data (LOD). The main objective of the research presented in this paper is to identify problems and tools used in the process of publishing LOD with the purpose of establishing a basis for the construction of a future framework that will help public institutions to facilitate such processes. To fulfill the objective, we conducted a systematic literature review in order to assess the state-of-the-art in this matter. The contribution of this work is to identify the frequent problems that arise in the LOD publishing process. It also provides a detail of the frameworks proposed in scientific papers grouping the technical tools by phases that correspond to the LOD publication life cycle. In addition, it compiles the characteristics of the ETL (Extract-Transform-Load) tools that predominate in this review, such as Pentaho Data Integration (Kettle) and OpenRefine.